Thermal Effects on Fines Migration: Insights from Sand Pack Experiments - Fernando Rengifo Barbosa; Rahman Miri; Mahmood Salimi; Alireza Nouri (Energies)
Mobilisation of in situ fine particles within oil sands reservoirs plays a critical role in permeability reduction and pore throat blockage, ultimately impairing reservoir performance and diminishing well productivity during thermal recovery operations. Variations in reservoir fluid conditions, such as changes in salinity and temperature, trigger the detachment, transport, and redeposition of fines within porous media. This study introduces a novel high-pressure high-temperature (HP-HT) sand retention testing (SRT) facility designed for evaluating formation damage by fines migration in SAGD producer wells, under salinity change and elevated temperature conditions. Such an integrated approach accounting for conditions closer to near-wellbore SAGD producers has not been explored in previous SRT methodologies. Laboratory tests were conducted on synthetic sand mixtures replicating the particle size distribution (PSD) and sand composition of the McMurray Formation, packed over a slotted liner coupon as a common sand control device used in SAGD producer wells. Produced fines concentration analysis, permeability measurements, and post-mortem retention profile analysis were employed to explain the fines transport mechanisms. The results highlighted the influence of repulsive electrostatic forces in mobilising, transport mechanisms and retention of fine particles at elevated temperature and low salinity conditions. The findings of this paper provide a deeper understanding of fines migration in SAGD reservoirs, delivering insights for optimising field strategies to mitigate fines-related flow restrictions and enhance bitumen recovery efficiency.